Wheat production in the highlands of Eastern Ethiopia: opportunities, challenges and coping strategies of rust diseases. (31st December 2022) - Nigus, Mulu; Shimelis, Hussein; Mathew, IsacK.; Abady, Seltene
ABSTRACT: Ethiopia is the primary wheat producer in Sub-Saharan Africa (SSA) owing to the suitable agro-ecological conditions. Despite wheats economic potential for food security, the actual yield under smallholder farmers conditions is low due to various production constraints. Thus, the objectives of this study were to assess the present wheat production opportunities and constraints and identify farmer-preferred traits to guide variety design with stem rust-resistance and economic traits in eastern Ethiopia. Data on production constraints and trait preferences were collected using structured questionnaires involving 144 wheat-producing farmers. Wheat rust (reported by 97.3% of respondents), small land size (90.4%) and a lack of improved varieties (75.6%) were identified as the major constraints. About 41.7% of respondents in the West-Hararghe and 27.8% in the East-Hararghe zones did not use crop protection strategies to control rusts. Substantial respondent farmers used cultural practices (18.8%), rust-resistant cultivars (13.2%) or, a combination of these (10.4%) to control rust diseases. The essential farmer preferred traits in a wheat variety were rust resistance, high yield potential and good quality grain for bread making. Therefore, there is a need to breed new varieties with high grain yield and quality and durable rust resistance for sustainable wheat production in eastern Ethiopia.